Mediating Effect of Workplace Stress on the Relationship between Perceived Organizational Support and Organizational Commitment among Malaysian Manufacturing Employees - Wong, Fock Keong (2024)
The purpose of the current research was to analyze organizational commitment and to predict the factors that influenced organizational commitment, with workplace stress serving as the mediator. In addition, this research introduced a novel conceptual framework to enhance the understanding of organizational commitment. Most previous studies on organizational commitment, the dependent variable, focused on establishing the direct relationship between the independent variables (predictors) and the dependent variable. However, there was insufficient research to examine the "indirect" relationship between the predictors and the dependent variable. Therefore, this research sought to address this gap by using workplace stress as a mediator to determine whether an indirect relationship existed, which enhanced the understanding of the connection between the predictors and the dependent variables. The theoretical framework of this research was the Job Demands-Resources (JD-R) Theory. Furthermore, the current researcher utilized various elements to anticipate both workplace stress and organizational commitment, including job characteristics, perceived organizational support, and work engagement. The current research adopted both Statistical Package for the Social Sciences (SPSS) and partial least squares structural equation modelling (PLS SEM) as the research method for data analysis. The expected outcome of the study was to determine whether the hypotheses tested were accepted or rejected. The significance of the findings in the study contributed to the literature on factors that could enhance organizational commitment. The results showed a significant relationship between perceived organizational support, workplace stress, and organizational commitment. However, the tested relationships between job characteristics, work engagement, and organizational commitment were found to be not significant. The findings indicated that workplace stress played a strong mediating role between job characteristics, perceived organizational support, work engagement, and organizational commitment.